BASIC PRINCIPLES OF ISLAMIC EDUCATION: MUHAMMAD NATSIR'S THOUGHT ON THE QUALITY COMMUNITY DEVELOPMENT - Jarudin Jarudin; Edwar Kemal (LLDIKTI Wilayah X, 2023)
This study investigated Muhammad Natsir's thoughts on education, specifically on the basic principles of Islamic education by using the historical tracing method. Data sources were examined through library research due to materials from readings and references to relevant books and manuscripts. Based on the study, it was discovered that Muhammad Natsir laid down five basic principles and concepts of Islamic education in the following: first, tawhid as the foundation of education; second, the position of science is placed after tawhid, which serves as a reinforcement of faith; third, tradition and discipline of thought; fourth, mastery of Arabic; and the necessity of Islamic educational institutions has a crucial role as a facility and a place to actualize these four concepts.